Impacts of soil–aquifer heat and water fluxes on simulated global climate - N. Y. Krakauer; M. J. Puma; B. I. Cook (Hydrology and Earth System Sciences, 2013)
Climate models have traditionally only represented heat and water fluxes within relatively shallow soil layers, but there is increasing interest in the possible role of heat and water exchanges with the deeper subsurface. Here, we integrate an idealized 50 m deep aquifer into the land surface module of the GISS ModelE general circulation model to test the influence of aquifer–soil moisture and heat exchanges on climate variables. We evaluate the impact on the modeled climate of aquifer–soil heat and water fluxes separately, as well as in combination. The addition of the aquifer to ModelE has limited impact on annual-mean climate, with little change in global mean land temperature, precipitation, or evaporation. The seasonal amplitude of deep soil temperature is strongly damped by the soil–aquifer heat flux. This not only improves the model representation of permafrost area but propagates to the surface, resulting in an increase in the seasonal amplitude of surface air temperature of > 1 K in the Arctic. The soil–aquifer water and heat fluxes both slightly decrease interannual variability in soil moisture and in land-surface temperature, and decrease the soil moisture memory of the land surface on seasonal to annual timescales. The results of this experiment suggest that deepening the modeled land surface, compared to modeling only a shallower soil column with a no-flux bottom boundary condition, has limited impact on mean climate but does affect seasonality and interannual persistence.